Co-therapy in a group setting : benefits and challenges in facilitating co-therapy music therapy in a small group setting : exegesis submitted in partial fulfilment of the requirements for the degree of Masters of Music Therapy, New Zealand School of Music - Katz, Yair (Massey University, 2012)
This study provides my findings on the issue of co-therapy in music therapy practice with children and young adults, based on my personal experience in placement during my final year as a student practitioner for music therapy. The study discusses co-therapy from the point of view that, like any other example of team work, co-therapy has advantages and benefits, as well as disadvantages, difficulties and challenges. The study looks at the practice of co-therapy in detail, to reach conclusions about those benefits and challenges. It uses examples of co-therapy with small groups of clients with a range of different needs, to provide a wide picture of how co-therapy could be used effectively in music therapy, but also to discuss the issues that occurred when co-facilitating. The results of the analysis are presented in the findings section and discussed in the subsequent section. It is important to note that these results, as in other qualitative research studies, are based on personal interpretations and should not be viewed as facts. They can, however, serve as recommendations and points for consideration for students, new and experienced practitioners who might consider co-therapy as a practice.
Keywords: Music therapy for children; Music therapy for teenagers; Multiple psychotherapy; Research Subject Categories::HUMANITIES and RELIGION::Aesthetic subjects::Music; Co-therapy